The impact of self-confidence, creativity and vision on leadership performance: perceptions at Ecuadorian SMEs owner - managers - García-Vidal, Gelmar; Sánchez-Rodríguez, Alexander; Pérez-Campdesuñer, Reyner; Martínez-Vivar, Rodobaldo (Serbian Journal of Management, 2019)
Leadership performance is an important component for small and median enterprises long-term viability. As a complex phenomenon, leadership performance is affected by many other variables, including the perception of owners - managers of their own behavior as leaders. This study examines the perceived impact of self-confidence, creativity and vision of owner/ managers on leadership performance, for which 334 individuals participating from the three most significant economic sectors of the studied area were surveyed. The results indicate that self-confidence has a positive, strong and significant relationship with the ability of the owner/managers to articulate a vision and influence their subordinates, but not the creativity whose relationship, although positive and significant, is not considered strong. In addition, a strong, positive and significant relationship was found between the ability to articulate a vision and influence its subordinates and the leadership performance.